Sign in
Please select an account to continue using cracku.in
↓ →
If $$(x) = x^{2} + 6x + K_{1}$$ and $$g(x) = x^{2} + 5x + K_{2}$$ have common factor $$x - a =$$ then a =
$$K_{2} - K_{1}$$
$$K_{1} + K_{2}$$
$$\frac{K_{1} + K_{2}}{2}$$
$$2(K_{1} + K_{2})$$
Create a FREE account and get:
Terms of Service
CAT Formulas PDFCAT Syllabus PDFCAT Study Plan PDFCracku Brochure
Detailed syllabus & Topic-wise Weightage
By proceeding you agree to create your account
Free CAT Syllabus PDF will be sent to your email address soon !!!